2021
DOI: 10.1108/ijppm-08-2020-0419
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy multi-criteria framework to identify barriers and enablers of the next-generation vaccine supply chain

Abstract: PurposeDue to the introduction of new vaccines in the child immunization program and inefficient vaccine supply chain (VSC), the universal immunization program (UIP), India is struggling to provide a full schedule of vaccination to the targeted children. In this paper, the authors investigate the critical factors for improving the performance of the existing VSC system by implementing the next-generation vaccine supply chain (NGVSC) in India.Design/methodology/approachThe authors design a fuzzy multi-criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…This will also help in better forecasting as well as the implementation of new management techniques in VSC. The study of Chandra et al. (2021) also revealed that in the future, with the inclusion of new vaccines, more VSC professionals with the necessary technical and leadership skills will be required to operate the VSC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will also help in better forecasting as well as the implementation of new management techniques in VSC. The study of Chandra et al. (2021) also revealed that in the future, with the inclusion of new vaccines, more VSC professionals with the necessary technical and leadership skills will be required to operate the VSC.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis shows that the Operational challenge (O) was weighted highest, followed by, Strategical challenge (S), Technological challenge (T), Social challenge (So), and Environmental challenge (O > S > T > So > E) as given in Table 4. The Previous studies on regular immunization programs have also underlined the severity of operational challenges (Chandra et al. , 2021; Chandra and Kumar, 2020), but the emergency of COVID-19 amplified this.…”
Section: Resultsmentioning
confidence: 99%
“…They explored the conditions under which the two members would be willing to accept the strategy. Chandra et al (2021) investigated the critical factors for improving the performance of the existing VSC system by implementing the next-generation vaccine supply chain (NGVSC) in India. The outcome of the analysis contends that demand forecasting is the topmost supply chain barrier and sustainable financing is the most critical enabler to facilitating the implementation of the NGVSC.…”
Section: Literature Review and Related Workmentioning
confidence: 99%
“…It is crucial to know which metrics are most helpful in measuring and tracking the quality and effectiveness of a vaccine (e.g. transmission rates, case fatality, adverse effects) and to outline how these data can be noted in real-time to other countries (Chandra et al. , 2021; Mio et al.…”
Section: Hypothesis Developmentmentioning
confidence: 99%